Maternal Health Care Awareness Among College Girls of other Backward Class of Central India - Nema, Anjna; Sharma, K.K.N. (International Journal of Child Health and Nutrition, 2013)
Death due to complication related to pregnancy and childbirth are the leading cause of mortality of women in the reproductive ages in developing countries. Health status of Madhya Pradesh in India shows IMR/1000 live births is 90 and < 5 mortality / 1000 is 137.6. [1] India is among "Slow progressing nation” in child and maternal care. Madhya Pradesh is one of the states where maternal mortality rates are as high as 700 or more [2]. Antenatal and postnatal care awareness among youth can certainly reduce the mortality and morbidity rate, as they are future mothers. Objective: The study has been undertaken to find the knowledge and awareness among 250 college girls of other backward class, Jabalpur city, Madhya Pradesh regarding antenatal and postnatal health care. Study Area: India is the seventh biggest country of the world. It has 2.4 percent land area and 16.7 percent population of the whole world. Madhya Pradesh is one of the major state of India located in the central part of India therefore it is named so. It has 6, 03, 85,118 total population out of which 2, 89, 28,245 are female. Jabalpur city is the heart of India, and a Division of Madhya Pradesh The population of Jabalpur is 2,167,469. Sample: 250 randomly selected other backward class category college girls of Jabalpur city, Madhya Pradesh, India are the sample for the present study. Other backward class (OBCS) is one of socially disadvantaged groups. Method: For recording information regarding knowledge & perception towards maternal health care, a detailed structured but simple questionnaire was distributed among 250 randomly selected unmarried college girls of other backward class of Jabalpur city, Madhya Pradesh, India. Sample colleges were selected by stratified random sampling method. The study was conducted in various colleges in Jabalpur. Results: It is found that all 100 percent girls are aware that pregnant women need special care. 60.8 percent girls consider pregnancy as a general physiological process, 74.8 percent accepted that during pregnancy normal daily routine work should be done. 89.6 percent girls have a view for monthly consultation to Doctor during pregnancy. 66.4 percent knew tetanus toxoide injection is necessary in pregnancy.70.4 percent girls have knowledge that folic acid tablets are given to prevent anemia.96 percent girls accepted that in pregnancy extra nutrient should be given. 56.6 percent girls mentioned all the nutrients should be given in extra amount during pregnancy period.15.8 percent girls consider protein 12.0 percent girls iron, 12.0 percent girls calcium and 3.3 percent girls consider Vitamin A should be given in extra amount. 24 percent girls knew that weight of normal neonate is 3 kg. All the girls accepted that mother’s milk should be first feed of new born babies. Only 51.2 percent girls have knowledge regarding colostrums. 28.8 percent girls are aware that 6 months is correct age for infant to introduce semisolid food.17.6 percent girls knew 4 months is correct age for supplementary food. 91.2 percent girls correctly mentioned salt-sugar solution could be given for treatment of diarrhea at home. 97.6 percent students are having knowledge of oral rehydration solution. Conclusion: It has been noticed that girls are quite aware of antenatal and postnatal care. It is suggested regarding important aspects, which are lacking like, colustrum or nutritional requirement of a mother, students should be informed by interpersonal communication. Parents should also pass their knowledge acquired by them through the experience of life realizing that maternal health is a major instrument of social and economic development and plays an important role in the creation of a new world through safe motherhood.